Widespread pain syndrome in long COVID-19: melatonin as an adjuvant treatment - Souissi, Amine; Prieto-González, Pablo; Ben Saad, Helmi (Frontiers in Pain Research, 2025)
Long coronavirus disease 2019 (LC19) represents a complex global health challenge. Survivors frequently report persistent problems like widespread pain syndrome (WPS), cognitive dysfunction, cardiovascular complications, and sleep disturbances. These health problems, which are worsened by oxidative stress and inflammaging, open the prospect of treatment strategies targeting these mechanisms. Melatonin is a potential option for treating LC19 problems because of its anti-inflammatory, antioxidant, and pain-modulating properties. Melatonin targets shared pathological pathways, offering a promising approach to reducing inflammation, oxidative stress, and neuroendocrine dysfunction. The present mini-review explores the therapeutic potential of melatonin in the treatment of LC19, focusing on its effects on WPS and inflammation.